Optimization parameters of a part of accelerating structure with drift tubes prestripping section the MILAC heavy ion linear accelerator - Bomko, V.O.; Zajtsev, B.V.; Kobets, A.P.; Meleshkova, Yu.V. (Вопросы атомной науки и техники, 2014)
Investigations on optimization of parameters of a part of accelerating structure with drift tubes prestripping section PSS-20 for acceleration of heavy ions with the relation of their mass to charge A/q≤20 are prolonged. On the second part of acceleration of ions from 150 keV/ nucl. up to 1 MeV/ nucl. the highest rate of acceleration is created interdigital-H (IH) accelerating structure with drift tubes. Radially-phase stability of the accelerated bunch of ions is provided with a combination of alternative phase focusing with updating of high-frequency focusing. Продолжены исследования по оптимизации параметров участка ускоряющей структуры с трубками дрейфа предобдирочной секции ПОС-20 для ускорения тяжёлых ионов с отношением их массы к заряду A/q≤20. На втором участке ускорения ионов от 150 кэВ/нукл. до 1 МэВ/нукл. наиболее высокий темп ускорения создаёт встречно-штыревая ускоряющая Н-структура с трубками дрейфа. Радиально-фазовая устойчивость ускоренного пучка ионов обеспечивается комбинацией переменно-фазовой фокусировки с модификацией высокочастотной фокусировки. Продовжені дослідження з оптимізації параметрів ділянки прискорюючої структури із трубками дрейфу передобдиркової секції ПОС-20 для прискорення важких іонів з відношенням їх маси до заряду A/q≤20. На другій ділянці прискорення іонів від 150 кеВ/нукл. до 1 МеВ/нукл. найбільш високий темп прискорення створює зустрічно-штирьова прискорююча Н-структура із трубками дрейфу. Радіально-фазова стійкість прискореного пучка іонів забезпечується комбінацією перемінно-фазового фокусування з модифікацією високочастотного фокусування.